Glacier data - summit elevation from Kebnekaise south summit - Tarfala Research Station (Stockholm University, 2020)
Tarfala Research Station (2020). Glacier data - summit elevation from Kebnekaise south summit, 1968–2020 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/2jVbFrAZisV44hwgrbSLzY6Z
Keywords: Tarfala Research Station; Glacier elevation/ice sheet elevation; Glaciers; Elevation; Elevation; Year; Year; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap